Case report: SARS-CoV-2 infection as a trigger for diabetic ketoacidosis and newly detected pancreatic autoantibodies - Mishra, Rahul; Elshimy, Ghada; Kannan, Lakshmi; Jacob, Aasems; Raj, Rishi (Frontiers in Endocrinology, 2022)
A 39-year-old-woman with a past medical history of type 2 diabetes mellitus (T2DM) on oral hypoglycemic agents presented to the emergency room with nausea, vomiting, shortness of breath, and altered mental status. Seven days prior to presentation, she was diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Laboratory workup on presentation confirmed the diagnosis of diabetic ketoacidosis (DKA) (Blood glucose 523 mg/dL, beta-hydroxybutyrate 8.91 mmol/L, pH 6.9, bicarbonate 11 mEq/L, anion gap 25 mEq/L, and HbA1c 10.8 %). She was managed for DKA with hydration and insulin drip and discharged home. However, to our surprise, at the 2-week follow-up visit, she was found to have positive antibodies for zinc transporter 8 (ZnT8). The rest of her antibodies associated with T1DM were negative. She was therefore started on a basal-bolus regimen and managed as type 1 diabetes mellitus (T1DM). Our case illustrates that there is an increased risk of T1DM following infection with SARS-CoV-2.